FUNGSI ETIKA PROFESI HUKUM BAGI ADVOKAT DALAM MENEGAKKAN HUKUM - Edi Krisharyanto (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
As one of legal officials, lawyers are expected to carry out their duty professionally give the best service to their client. Besides giving advice of proper regulations to the public as one of their responsibilities, moral and ethics also play very important roles for lawyers to uphold the law.